Optical coherence tomography in the diagnosis of glaucomatous optical neuropathy in children with primary congenital glaucoma - L. A. Katargina; N. N. Arestova; E. N. Demchenko; A. Yu. Panova; A. A. Sorokin (Российский офтальмологический журнал, 2023)
Purpose: to analyze morphometric, clinical and functional manifestations of glaucomatous optical neuropathy in congenital childhood glaucoma (CG).Material and methods. We examined 103 children (163 eyes) with (CG), including 54 children (86 eyes) with primary congenital glaucoma (PCG) aged 1 month to 17 years. In addition to the regular ophthalmological examination, we performed optical coherence tomography of the optic nerve head (ONH), flash visual evoked potentials, total and rhythmic electroretinogram, oscillatory potentials (OP), echobiometry of the eye axial length.Results. The thickness of the retinal nerve fiber layer peripapillary (pRNFL) ranged from 32 to 120 μm, averaging 71.67 ± 18.2 μm. The thinning was detected in 83.0% of cases, primarily in the temporal sectors (90.6%). As the condition progressed, a tendency to progressive thinning of the RNFL was detected. The minimum rim width (BMO-MRW) ranged from 87 to 336 μm and was reduced in most children (14 out of 16, 87.5%). A strong inverse correlation of the neuroretinal rim with the depth (r = -0.69) and the width (r = -0.93) of the excavation was detected. Also, a strong direct correlation was established between the minimum neuroretinal rim width reduction and the thickness of the BMO-MRW and pRNFL (r = 0.79), as well as the upper and lower temporal sectors (r = 0.81 and r = 0.88, respectively). The thickness of the ganglion cell (GC) layer varied from 8 to 23 μm and averaged 14.64 ± 4.89 μm, with a reduction recorded in most cases (64.7%). All patients showed a decrease in oscillatory potentials (OP) by 40% or more (6.31 ± 2.33) as compared to the control group (20.24 ± 6.28). Thinning of the RNFL was registered in these eyes in 90.6% of cases averagely (p < 0.05) and in the upper and the lower temporal sectors (p < 0.05).Conclusion. RNFL thickness, the minimal width of the BMO-MRW and the OP are the most sensitive criteria to assess the degree of glaucomatous optic neuropathy in children with PСG. The study of the GC layer thickness can serve as an additional diagnostic criterion of assessing the state of the ONH.